Insights of the qualified exomars laser and mechanical considerations of its assembly process - Ribes-Pleguezuelo, Pol; Guilhot, Denis; Basset, Marta Gilaberte; Beckert, Erik; Eberhardt, Ramona; Tünnermann, Andreas (Instruments, 2019)
1960 is the birth year of both the laser and the Mars exploration missions. Eleven years passed before the first successful landing on Mars, and another six before the first rover could explore the planet’s surface. In 2011, both technologies were reunited with the first laser landing on Mars as part of the ChemCam instrument, integrated inside the Curiosity Rover. In 2020, two more rovers with integrated lasers are expected to land on Mars: one through the National Aeronautics and Space Administration (NASA) Mars 2020 mission and another through the European Space Agency (ESA) ExoMars mission. The ExoMars mission laser is one of the components of the Raman Spectrometer instrument, which the Aerospace Technology National Institute of Spain (INTA) is responsible for. It uses as its excitation source a laser designed by Monocrom and manufactured in collaboration with the Fraunhofer Institute for Applied Optics and Precision Engineering (IOF). In this paper, we present for the first time the final flight module laser that has been installed in the rover’s onboard laboratory and validated to be shipped to Mars in 2020. Particular emphasis is given to mechanical considerations and assembly procedures, as the ExoMars laser assembly has required soldering techniques in contrast to the standard adhesive technologies used for most laser assembly processes in order to fulfill the environmental and optical requirements of the mission.
CRIS-Team Scopus Importer:2023-04-20
Keywords: European space agency; ExoMars laser; Mars exploration; Raman spectroscopy; Solderjet bumping